2011
DOI: 10.3892/or.2010.1083
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus and non-muscle invasive urothelial bladder cancer: Potential relationship from a pilot study

Abstract: Abstract.The relationship between urothelial bladder cancer and high-risk human papillomaviruses (HR-HPV) is still a poorly understood entity, even if some studies have supposed a probably correlation. The aim of the present study was to assess the potential relationship between the presence of HR-HPV and non-muscle invasive urothelial bladder cancers (NMIBC). One hundred and thirty-seven subjects (78 patients affected by NMIBC and 59 controls) were recruited in this prospective study. HR-HPV DNA was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…In contrast to our findings and the previously mentioned reports, others have shown a positive correlation between high-risk HPV infection and high-grade urothelial cancers of the bladder. [7][8][9]35,36 Cai et al 37 have proposed that HPV may have a causative role in the genesis of urothelial neoplasms, particularly in nonmuscle-invasive bladder cancer. In our study, we detected p16 expression in 31% (13/42) of cases of urinary bladder squamous cell carcinoma and in 33% (9/27) of cases of urinary bladder urothelial carcinoma with squamous differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to our findings and the previously mentioned reports, others have shown a positive correlation between high-risk HPV infection and high-grade urothelial cancers of the bladder. [7][8][9]35,36 Cai et al 37 have proposed that HPV may have a causative role in the genesis of urothelial neoplasms, particularly in nonmuscle-invasive bladder cancer. In our study, we detected p16 expression in 31% (13/42) of cases of urinary bladder squamous cell carcinoma and in 33% (9/27) of cases of urinary bladder urothelial carcinoma with squamous differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…The reported findings have been conflicting and inconclusive. [17][18][19][20][21][22] It has also been proposed that HPV may play a role in the development of inverted papilloma, on the basis of detection of HPV strains 16 and 18 in a number of these lesions. 23,24 The primary aim of this study was to examine a relatively large population of urothelial inverted papillomas for the presence of HPV infection using in situ hybridization (ISH) methods to provide more definitive evidence as to the etiologic role HPV may play in urothelial cells.…”
mentioning
confidence: 98%
“…In contrast, several studies stated that high risk-HPV (HR-HPV) should be considered as cofactor in urothelial bladder cancer. Cai et al have recently found a statistical significant difference in HR-HPV frequency between high-grade and lowgrade urothelial bladder cancer cases [40]. Also, Moonen et al found a higher infection rate in highgrade tumors and stated that the increase in infection rate in high-grade tumors suggests a relationship between tumor grade and high-risk HPV infection [29].…”
Section: Discussionmentioning
confidence: 99%